2000
DOI: 10.1109/10.871412
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional surface reconstruction and fluorescent visualization of cardiac activation

Abstract: Optical imaging of transmembrane potentials in cardiac tissue is a rapidly growing technique in cardiac electrophysiology. Traditional studies typically use a monocular imaging setup, thus limiting investigation to a restricted region of tissue. However, studies of large-scale wavefront dynamics, especially those during fibrillation and defibrillation, would benefit from visualization of the entire epicardial surface. To solve this problem, a panoramic cardiac visualization algorithm was developed which perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…This issue can be resolved, at least for epicardial reentry, using a mapping technology that images the entire epicardium, eg, panoramic mapping. 16 Another possible ex- planation is that sustained reentry is dependent on the size of the heart. We found that the hearts with sustained reentry were significantly smaller than the hearts without.…”
mentioning
confidence: 99%
“…This issue can be resolved, at least for epicardial reentry, using a mapping technology that images the entire epicardium, eg, panoramic mapping. 16 Another possible ex- planation is that sustained reentry is dependent on the size of the heart. We found that the hearts with sustained reentry were significantly smaller than the hearts without.…”
mentioning
confidence: 99%
“…These multiple points of view can be obtained with a single detector and mirror arrangement or with multiple detectors positioned around the heart. In the first systems implemented by Lin and Wikswo [7] and subsequently by Bray et al [3] a single optical detector was used in combination with two mirrors positioned at the back of the heart to show the reflected images of the posterior surface (Figure 10.1a). In this system, a CCD camera was used and a horizontal rectangular region of interest was implemented to collect all three views of the heart (reflected images simultaneously collected on either side of the direct image on the CCD chip).…”
Section: Panoramic Imaging Systemmentioning
confidence: 99%
“…To overcome these limitations, several groups have developed panoramic optical mapping systems [3][4][5]. The earliest implementations of panoramic imaging involved using multiple optical detectors to simultaneously image multiple views of the heart [6], or conversely, a single optical detector with a mirror arrangement to simultaneously image multiple views on the same detector [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The panoramic mapping system is used to map the entire epicardium of the rabbit heart [4][5][6][7] . This system provides a global view of the evolution of reentrant circuits during arrhythmogenesis and defibrillation, and has been used to study the mechanisms of arrhythmias and antiarrhythmia therapy 8,9 .…”
Section: Introductionmentioning
confidence: 99%